Attitudes of Mosul University Students (Married and Unmarried) Towards Parental Abandonment A Social Field Study in Mosul City - Haitham saeed Abdullah Omar Al-Khalidi dr. (Journal of College of Education, 2025)
The aim of the research is to identify the attitudes of Mosul University students (married and unmarried) towards abandoning parents and to reveal their attitudes in light of the variables of gender,marital status, academic stage, and academicspecialization. It is a descriptive analytical research, as it relied on the social survey method. To achieve the research objectives, a questionnaire was designed consisting of (43) paragraphs with five-point alternatives distributed over two axes. It was presented to a group of arbitrators to ensure its validity. After taking their comments into account, it was applied to a sample of (300) male and female students at the University of Mosul, distributed among six scientific and humanities colleges. The data was processed statistically, and the research concluded with a number of results, the most important of which are: Contents• University students have a close relationship and strong commitment to their parents, due to their need for security and stability, as parents are a source of safety and protection for their children.• The lack of a significant difference in parental abandonment is attributed to gender (male/female) , scientific or humanities specialization, and marital status (married/single), as parents are a source of love, affection, and care.• The research results revealed a strong emotional bond between children and parents.
Keywords: Trends, abandonment, parental abandonment, university students